2013
DOI: 10.1177/2165143412467666
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Special Education and Career and Technical Education Collaboration and Communication

Abstract: This study explored perceptions of current practices used by secondary educators (special education teachers and guidance counselors) and stand-alone career and technical education (CTE) centers when working with students with disabilities from sending high schools participating in secondary CTE from one midwestern state. The study looked at perceptions held by each educational setting (high school and secondary CTE) regarding needs and responsibility when working with these shared students. Study participants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 11 publications
1
19
0
Order By: Relevance
“…CTE particularly emphasizes curricula integrating information technology literacy into career readiness exploration (see, for example, Izzo, Yurick, Nagaraja, & Novak, 2010). Despite this promise, exploratory findings on the relationships between CTE staff and special educators show inconsistent communication, including conflicting terminology, as well as a general lack of understanding of responsibilities in sharing student information and support services (Schmalzried & Harvey, 2014). As is the case with all content areas, collaboration among special educators and classroom teachers will be crucial in promoting the six domains of CCR.…”
Section: Discussionmentioning
confidence: 99%
“…CTE particularly emphasizes curricula integrating information technology literacy into career readiness exploration (see, for example, Izzo, Yurick, Nagaraja, & Novak, 2010). Despite this promise, exploratory findings on the relationships between CTE staff and special educators show inconsistent communication, including conflicting terminology, as well as a general lack of understanding of responsibilities in sharing student information and support services (Schmalzried & Harvey, 2014). As is the case with all content areas, collaboration among special educators and classroom teachers will be crucial in promoting the six domains of CCR.…”
Section: Discussionmentioning
confidence: 99%
“…CTE capitalizes on these experiences for the general population, but there were only two studies that focused on students with ID in the literature review. In fact, one particular study found that community business professionals may be less willing to partner with high schools to create meaningful work experiences for adolescents with disabilities, as opposed to their peers without disabilities (Carter et al, 2009); meanwhile, another study showed a clear communication gap between responsibilities of the professionals who work with SWD in CTE settings (e.g., special educators, CTE teachers), such as providing and sharing student information and coordinating services (Schmalzried & Harvey, 2014). Importantly, both of these articles highlight barriers in the current systems that leave this subgroup with more limited options for work experience.…”
Section: Employmentmentioning
confidence: 99%
“…Collaboration and communication are expressed areas of concern by secondary CTE and special education professionals alike (Harvey, Test, & Rowe, 2017). Schmalzried and Harvey (2014) recommended ongoing communication and collaboration concerning students with disabilities enrolled in secondary CTE settings. Haber and Sutherland (2008) suggested to facilitate communication administrators should: a.…”
Section: Ensure Communication Among Professionals Is Pro-mentioning
confidence: 99%
“…Perkins V addresses the need for professional development for CTE professionals on helping students with disabilities succeed in secondary CTE. Similarly, Schmalzried and Harvey (2014) suggested that special educators need to understand secondary CTE and provisions in Perkins V regarding special populations, including students with disabilities. Therefore, we offer six recommendations for providing collaborative personnel preparation and professional development.…”
Section: Recommendationsmentioning
confidence: 99%